The influence of the personal learning environment (PLE) approach on english speaking ability - Situmorang, Idawati; Sitompul, Hamela Sari; Tuty, Tuty (Cendikia : Media Jurnal Ilmiah Pendidikan, 2024)
The aim of this research is to determine the effect of the Personal Learning Environment (PLE) Approach on English Speaking Ability. The concept of the Personal learning environments (PLE) approach will make learning individuals become a subject. Each person is both a teacher and a student who can decide the direction of the learning. The method used in this research was an experimental method using two class groups. The research instrument used was a written test. Based on the results of data analysis, it can be concluded that the average score for English speaking skills in the control class is 53.7. Furthermore, in testing the t test hypothesis, a sig of 0.00 was obtained. Based on the conclusion, if the sig (2-tailed) value is <0.05, then there is a significant difference. Meanwhile, the average value of English speaking skills for the experimental class is 80.1. So, it can be concluded that there is an influence.